2014
DOI: 10.1177/0272989x14529846
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 4 Pediatric Health-Related Quality-of-Life Instruments

Abstract: Background Few studies have compared multiple health-related quality of life (HRQOL) instruments simultaneously for pediatric populations. This study aimed to test psychometric properties of four legacy pediatric HRQOL instruments: the Child Health and Illness Profile (CHIP), the KIDSCREEN-52, the KINDL, and the Pediatric Quality of Life Inventory (PedsQL). Methods This study used data of 908 parents whose children (ages 2–19) were enrolled in Florida Medicaid. Parents were asked via telephone interview to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 47 publications
(102 reference statements)
0
31
0
Order By: Relevance
“…Several studies that examined the association between pain and HRQOL among adolescents showed that persistent pain is associated with reduced HRQOL [10,20,[22][23][24][25]. There are several questionnaires that measure HRQOL, of which KIDSCREEN-52 has been shown to have the best structural validity [26]. However, there is limited research investigating HRQOL and pain in a school-based population of adolescents using the 10 sub-scales of the KIDSCREEN-52 questionnaire [27].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies that examined the association between pain and HRQOL among adolescents showed that persistent pain is associated with reduced HRQOL [10,20,[22][23][24][25]. There are several questionnaires that measure HRQOL, of which KIDSCREEN-52 has been shown to have the best structural validity [26]. However, there is limited research investigating HRQOL and pain in a school-based population of adolescents using the 10 sub-scales of the KIDSCREEN-52 questionnaire [27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, good generic instruments should be able to assess the HRQoL in children with varying health conditions and across different languages and cultures [12] , [13] . Using a large sample of children enrolled in the Medicaid program, our previous study based on the classical test theory (CTT) method suggested that none of the existing pediatric HRQoL instruments (the CHIP, KIDSCREEN, KINDL-R, or PedsQL) was superior to any other in the different psychometric properties [14] , [15] . Although the CTT has often been applied to compare or develop new HRQoL instruments, the use of the CTT alone may neglect item-level information, which might bias the conclusions in comparative effectiveness research and clinical applications [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Many of these did not contain the dimensions recommended by the World Health Organization to be central to the definition of QoL. Kenzik et al undertook a comparison of the KINDL, the KIDSCREEN-52, the PedsQL and the Child Health and Illness Profile [49]. The authors administered these questionnaires in an observational study and investigated structural, convergent/discriminant, and known-group validities.…”
Section: Hrqol Definition and Conceptualisation In Childrenmentioning
confidence: 99%